Using poly(3,4-ethylenedioxythiophene) polystyrene sulfonate surfaces to develop an electroanalytical sensor for therapeutic monitoring of tricyclic-antidepressants - Gibney, Steven (2022)
This project aims to develop an electroanalytical sensor capable of measuring the real-time concentration of tricyclic antidepressants (TCA) in complex biological environments. Advances in micro- and nano- scale engineering have opened new avenues of sensor development; it is now possible to design sensors which function in vivo. The ability to accurately measure the concentration of an analyte in vivo provides crucial information about the pharmacokinetic behaviour of an analyte, while avoiding the need for repeated and potentially difficult sampling procedures. The main challenges which limit the development of an in vivo sensing device are caused by immune response, inflammation and surface contamination, all of which can prevent a sensor from functioning. To overcome these challenges a multidisciplinary approach must be used. Through a combination of electroanalytical chemistry and biomaterial development I have attempted to design and develop a sensing platform capable of the in vivo detection and monitoring of tricyclic antidepressant (TCA).